Digital Technology and Work Discipline Effects on MSME Work Motivation, West Jakarta - Muhammad Rizki Akbar; Immanuel Harri; Enrico Hario Bimo; Nopriadi Saputra (Penerbit Goodwood, 2024)
Purpose: The COVID-19 pandemic forced Indonesian MSMEs to rapidly adopt digital tools while disrupting conventional work discipline routines. This study examines the effects of digital technology (X1) and work discipline (X2) on work motivation (Y) among MSME operators in Kebon Jeruk Sub-District, West Jakarta, and tests the effect of digital technology on work discipline.Methodology: A quantitative correlational survey design was employed using simple random sampling on 975 registered MSME operators, yielding a sample of 103 respondents. Data were collected through structured Likert-scale questionnaires and analyzed using IBM SPSS Statistics version 22, incorporating validity and reliability testing, Kolmogorov-Smirnov normality testing, Pearson correlation, and simple linear regression.Results: Digital technology positively and significantly affects work motivation (r = 0.334, p = .001) and work discipline (r = 0.403, p = .0001). Work discipline does not significantly affect work motivation (r = 0.187, p = .059).Conclusions: Digital technology is the dominant driver of both work motivation and work discipline in this pandemic context. Limitations: The study covers one sub-district during the pandemic, limiting generalizability, and omits control variables including leadership quality and compensation.Contributions: This study provides empirical evidence on the dual motivational and disciplinary function of digital technology for Indonesian MSMEs during forced digital transformation, informing evidence-based digital literacy policy for small business operators.